Discovery of Brain-Penetrant, Irreversible Kynurenine Aminotransferase II Inhibitors for Schizophrenia - Dounay, Amy B; Anderson, Marie; Bechle, Bruce M; Campbell, Brian M; Claffey, Michelle M; Evdokimov, Artem; Evrard, Edelweiss; Fonseca, Kari R; Gan, Xinmin; Ghosh, Somraj; Hayward, Matthew M; Horner, Weldon; et al. (ACS medicinal chemistry letters, 2012)
Kynurenine aminotransferase (KAT) II has been identified as a potential new target for the treatment of cognitive impairment associated with schizophrenia and other psychiatric disorders. Following a high-throughput screen, cyclic hydroxamic acid PF-04859989 was identified as a potent and selective inhibitor of human and rat KAT II. An X-ray crystal structure and 13C NMR studies of PF-04859989 bound to KAT II have demonstrated that this compound forms a covalent adduct with the enzyme cofactor, pyridoxal phosphate (PLP), in the active site. In vivo pharmacokinetic and efficacy studies in rat show that PF-04859989 is a brain-penetrant, irreversible inhibitor and is capable of reducing brain kynurenic acid by 50% at a dose of 10 mg/kg (sc). Preliminary structure–activity relationship investigations have been completed and have identified the positions on this scaffold best suited to modification for further optimization of this novel series of KAT II inhibitors.